O chiado no Araguaia paraense : aspectos sociolinguísticos - Bazzo, Manoella Gonçalves (2024)
In Brazilian Portuguese, the fricative /S/ serves as a distinguishing feature among linguistic communities (Hora, 2002; Lucchesi, 2009; Scherre; Macedo, 1991), particularly concerning the variation between the alveolar [s, z] and alveopalatal [ʃ, ʒ] variants. In the state of Pará, the alveopalatal variant holds the status of a standard, marking the identity of people from Pará (Jesus; Mota, 2009a; Razky; Santos, 2020; Van Samson; Bentes, 2017). However, given the territorial dimension of the state, the realization of this variable is understood to be nonhomogeneous. Therefore, this research focuses on the Araguaia region of Pará, an Amazonian frontier area (Becker, 1988), with the objective of describing and interpreting the behavior of the archiphoneme /S/ in medial coda among speakers from this region; and as specific objectives: a) To create a database from the speech of participants from five municipalities within the region; b) To prepare phonetic-phonological data on the variable <S>, from the generated corpus; c) To process the collected data, quantitatively showing the incidence of the variants; d) To highlight the main linguistic and extralinguistic factors influencing the presence of the variation; and e) To analyze the perceptions and evaluations of the participants regarding elements that constitute the identity of the speech of Pará. Based on Variationist Sociolinguistics (Labov, 2008), the methodology involved the delimitation of five municipalities: Conceição do Araguaia, Redenção, Santana do Araguaia, Santa Maria das Barreiras and Xinguara. Semi-structured interviews were conducted and recorded with 79 participants aged between 19 and 60 years, from both urban and rural areas, of both genders, to develop the FALAPA database, which constituted the corpus of analysis. A variable rule analysis with mixed effects was performed using the statistical software R, in the RStudio interface. The results indicated that the realizations of the alveolar and alveopalatal fricatives exist in the researched community, with the first being indicated as the standard and more conservative variant, and the second as the innovative variant, which is more realized in stressed syllables and before /t/, and favored among men and younger people. Another observed aspect concerned stylistic monitoring, which showed a higher occurrence of the alveolar variant in more monitored contexts (reading newspaper articles and reading word lists), reinforcing the standard status of this variant. In the qualitative analysis, issues related to belonging and linguistic evaluation were observed, which overlapped with aspects of the identity of Pará. Participants evaluated the “chiado” (hissing) as something restricted to “people from the north of Pará”, despite the data indicating that it is also occurs in the Araguaia region of Pará under specific contexts; A strong sense of rejection of cultural aspects of Pará was evident among these participants, who feel inserted in a context of mixture and without their own identity, in a reality shaped by agribusiness.. Thus, unlike the northern regionof Pará, the alveolar variant retains the prestige of being the standard variant in Araguaia Paraense, while the alveopalatal variant emerges as an innovative variant, limited to the following linguistic context of /t/, resembling more closely the reality of northeastern and central-southern Brazilian communities.